MUC1 and CREB3 are Hub Ferroptosis Suppressors for Nucleus Pulposus and Annulus Fibrosus Degeneration by Integrated Bioinformatics and Experimental Verification - Yang X; Li Q; Wang L; Chen J; Quan Z (Dove Medical Press, 2024)
Xinyu Yang,1,2 Qiaochu Li,1,2 Linbang Wang,3 Jiaxing Chen,1,2 Zhengxue Quan1,2 1Department of Orthopedics, the First Affiliated Hospital of Chongqing Medical University, Chongqing, 400016, People's Republic of China; 2Orthopedic Laboratory of Chongqing Medical University, Chongqing, 400016, People's Republic of China; 3Department of Orthopedics, Peking University Third Hospital, Beijing, 100191, People's Republic of ChinaCorrespondence: Zhengxue Quan; Jiaxing Chen, Email quanzx18@126.com; cqykdxcjx@163.comPurpose: Ferroptosis is an underlying mechanism for various degenerative diseases, but its role in intervertebral disc degeneration remains elusive. This study aims to explore the key ferroptosis-related genes and its role in nucleus pulposus (NP) and annulus fibrosus (AF) degeneration.Methods: We analyzed the gene expression profiles of NP and AF from the Gene Expression Omnibus database. The ferroptosis-related differentially expressed genes (FRDEGs) in degenerated NP and AF were filtered, followed by GO and KEGG analysis. Feature FRDEGs were identified by the LASSO and SVM-RFE algorithms, and then Gene Set Enrichment Analysis (GSEA) and Gene Set Variation Analysis (GSVA) were conducted. Immune infiltration analysis was conducted by CIBERSORT algorithm. We established drug networks via the Drug-Gene Interaction Database and competitive endogenous RNA (ceRNA) networks via miRanda, miRDB, and TargetScan database. The expression levels of the feature FRDEGs were assessed by the validation sets, single-cell RNA-seq, and experimental verification.Results: A total of 15 and 18 FRDEGs were obtained for NP and AF, respectively. GO and KEGG analysis revealed their implication in oxidative stress. Four (AKR1C1, AKR1C3, MUC1, ENPP2) and five (SCP2, ABCC1, KLF2, IDO1, CREB3) feature genes were identified for NP and AF, respectively. The GSEA and GSVA analysis showed that these feature genes were enriched in lots of biological functions, including immune response. CREB3 in degenerated AF was negatively correlated with Eosinophils via CIBERSORT algorithm. The drugs and ceRNAs targeting CREB3 and MUC1 were identified. Experimental verification and single-cell RNA-seq analysis revealed that MUC1 and CREB3 were downregulated in degenerated NP and AF, respectively.Conclusion: MUC1 and CREB3 were considered novel biomarkers for NP and AF ferroptosis, respectively. Drug and ceRNA networks were constructed for future drug development and investigation of new mechanisms of ferroptosis.Keywords: bioinformatics analysis, experimental verification, ferroptosis, nucleus pulposus, annulus fibrosus, single-cell RNA-seq